UMP UC special plate numbers bid opens 1 February - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 28 January 2022 - The special registration plate number of Universiti Malaysia Pahang (UMP), UC, will be bid from 1 to 14 February.